Effects of greenfield, mergers and acquisitions, and corruption on environmental performance, and economic growth of eight selected SAARC and Asean countries - Farooq, Rana Muhammad Adeel (2018)
South Asian Association for Regional Cooperation (SAARC) and Association of Southeast Asian Nations (ASEAN) have received substantial foreign direct investment (FDI) inflows over the past few decades. However, these two regions have also experienced environmental degradation over the same period. Therefore, this study tests the validity of pollution haven hypothesis (PHH) by examining the influence of two types of FDI inflows namely greenfield investment and mergers and acquisitions (M&A), and the control of corruption on the environmental performance of eight selected countries in the SAARC and ASEAN regions over the 2003-2014 period. Additionally, using the endogenous growth model, this study investigates the impacts of greenfield investment, M&A, the control of corruption, and environmental performance on the economic growth of these eight countries over the same period. For the empirical analysis, this study employs fixed effect (FE), random effect (RE), two-stage least squares (2SLS) and robust standard errors (RSE) estimation methods. The results obtained from the FE and RE estimations prove that PHH is valid in these eight countries as shown by the detrimental consequences of greenfield investment on the environmental performance. Furthermore, the 2SLS estimation results indicate that greenfield investment and environmental performance positively and significantly contribute to the economic growth of these countries. Using a similar model but employing FE and RSE estimation methods, the results show that M&A, and control of corruption also accelerate the economic growth in these countries. The findings of this study are essential for policy purpose in that they can serve as a guide to formulate policies to attract energy-efficient and environment-friendly greenfield investment to enhance the environmental performance and accelerate the economic growth of these countries. Generally, SAARC and ASEAN countries should design policies for the improvement of the overall environmental performance and reduction in corruption to achieve rapid economic growth with sustainable environment.